Freshwater runoff effects on the production of biogenic silicate and chlorophyll-a in western Patagonia archipelago (50–51°S). (31st August 2020) - Torres, Rodrigo; Reid, Brian; Frangópulos, Máximo; Alarcón, Emilio; Márquez, Magdalena; Häussermann, Verena; Försterra, Günter; Pizarro, Gemita; Iriarte, José Luis; González, Humberto E.
Abstract: Freshwater discharged from the continent to the sea plays an important role in the biogeochemistry and productivity of the coastal ocean. The continental drainage basin characteristics can be a key local factor determining the concentration, proportions and timing of bio-active freshwater solutes discharged into an estuary, and thus could play a "bottom up" role modulating the phytoplankton assemblage attributes. In a period from 2015 to 2017 we characterize the concentration of total alkalinity (AT ) and silicic acid (DSi) in continental and estuarine surface waters at both limestone and silicates basins of the Madre de Dios archipelago (ca. 50–51°S and 75.5–75°W). Continental waters had high AT in limestone and low AT in silicate basins causing differences in the specific total alkalinity of estuarine waters. Similarly, while limestone continental water is characterized by very low DSi concentrations (3 ± 3 μM, n = 16) that dilute initial DSi concentrations of sub-Antarctic Surface Water (SAASW) at the mixing zone, continental water from silicate drainage basins (Patagonian Batholith; 53 ± 49 μM, n = 18) acts as a source of DSi to the estuary. Experimental SAASW dilution with two types of native continental water, one supplying high AT – low DSi and another supplying low AT – high DSi to the western central Patagonian Archipelago, resulted in phytoplankton assemblages with different characteristics. While "silicate-water" freshening of SAASW resulted in higher biogenic silicate (bSi) content, "limestone-water" freshening of SAASW resulted in higher levels chlorophyll a allocated in small cells-size range (0.45–2 μm). We suggest that the local variability in the suite of solutes delivered from continental runoff can significantly modulate phytoplankton communities attributes, especially in western Patagonian with interior estuarine waters characterized by extensive channels and fjords, together with extreme precipitation/runoff (>6 m y −1 ) and sharp contrasts in lithology. Graphical abstract: Image 1 Highlights: DSi and AT of the MDD continental water is a function of the lithology of the drainage basin. The lithology of the drainage basin forces the specific alkalinity of the estuarine waters of MDD. Limestone runoff are negligible sources of DSi for estuarine waters of MDD. Batholith runoff are important sources of DSi for the estuarine waters of MDD. The biological effects of "freshening" could be locally modulated by runoff's characteristics.